2021
DOI: 10.1093/rheumatology/keab625
|View full text |Cite
|
Sign up to set email alerts
|

Identification of distinct cytokine/chemokine profiles in dermatomyositis with anti-transcriptional intermediary factor 1-γ antibody

Abstract: Objectives Dermatomyositis (DM) and clinically amyopathic dermatomyositis (CADM) patients with positive expression of anti-transcription intermediary factor 1-γ (anti-TIF1-γ) antibody (Ab) are characterized by distinct clinicopathological features. We aimed to determine the role of cytokine/chemokine profiles in the classification of anti-TIF1-γ positive DM/CADM patients. Methods Serum levels of 24 cytokines/chemokines were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Notarnicola et al ( 31 ) observed increased serum levels of CCL2 in patients with idiopathic inflammatory myopathies, including ASS with anti-Jo-1 antibody. It has been proposed that serum CCL2 might be a good marker for disease activity in DM ( 16 , 29 , 32 35 ). Serum CCL2 was closely correlated with TNFR2 in DM and TIMP-1 in ASS.…”
Section: Discussionmentioning
confidence: 99%
“…Notarnicola et al ( 31 ) observed increased serum levels of CCL2 in patients with idiopathic inflammatory myopathies, including ASS with anti-Jo-1 antibody. It has been proposed that serum CCL2 might be a good marker for disease activity in DM ( 16 , 29 , 32 35 ). Serum CCL2 was closely correlated with TNFR2 in DM and TIMP-1 in ASS.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that TNF-α could participate in the pathogenic DM process [34]. Elevated TNF-α serum levels have been shown in anti-TIF1-γ antibody-positive DM patients suffering from significant muscle weakness and elevated cancer rate [35]. Our results were consistent with this finding which further revealed that plasma TNF-α levels in the Cancer TIF1-γ-DM group were significantly higher than in the Non-cancer TIF1γ-DM and HC groups (Figures 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…DM is predominantly mediated through humoral immunity involving B cells, CD4 + T cells, macrophages, muscle infiltration, antibodies, and complement-mediated injury of capillaries accompanied by inflammatory cytokine dysregulations [9,10]. Positive correlations between disease severity and serum cytokine levels, including C-X-C motif chemokine ligand 10 (CXCL10), C-C motif chemokine ligand 2 (CCL2), Galectin-9, interleukin-18 (IL-18), tumor necrosis factor-α (TNF-α), and TNF receptor 1 (TNFR1) were observed within anti-TIF1-γ antibody-positive DM patients [11]. Autoimmune diseases and cancer have a robust inflammatory background mediated by inflammatory cytokines despite displaying fundamentally different pathological conditions [12].…”
Section: Introductionmentioning
confidence: 99%